Electrophysiological Effects of Transcranial Direct Current Stimulation on Neural Activity in the Rat Motor Cortex - Tanaka, Tomoko; Isomura, Yoshikazu; Kobayashi, Kazuto; Hanakawa, Takashi; Tanaka, Satoshi; Honda, Manabu (Frontiers in Neuroscience, 2020)
Transcranial direct current stimulation (tDCS) is a non-invasive technique that modulates the neuronal membrane potential. We have previously documented a sustainable increase in extracellular dopamine levels in the rat striatum of cathodal tDCS, suggesting that cathodal tDCS enhances the neuronal excitability of the cortex. In the present study, we investigated changes in neuronal activity in the cerebral cortex induced by tDCS at the point beneath the stimulus electrode in anesthetized rats in vivo. Multiunit recordings were performed to examine changes in neuronal activity before and after the application of tDCS. In the cathodal tDCS group, multiunit activity (indicating the collective firing rate of recorded neuronal populations) increased in the cerebral cortex. Both anodal and cathodal tDCS increased the firing rate of isolated single units in the cerebral cortex. Significant differences in activity were observed immediately following stimulation and persisted for more than an hour after stimulation. The primary finding of this study was that both anodal and cathodal tDCS increased in vivo neuronal activity in the rat cerebral cortex underneath the stimulus electrode.